Bullying Prevention Efforts at Muslimat NU 1 Ngebruk Kindergarten Through Parenting Programs - Shobahun Ni'mah; Sarah Emmanuel Haryono; Rina Wijayanti (Bulletin of Early Childhood, 2025)
Bullying in early childhood is a serious issue due to its negative impact on children's social and emotional development. This study aims to examine the role of parenting programs in preventing bullying behavior at TK Muslimat NU 1 Ngebruk. The research used a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results showed that forms of bullying included physical, verbal, and non-verbal types, frequently occurring in children’s daily school activities. The parenting program implemented by the school has been effective in increasing parents' understanding of the dangers of bullying and in strengthening positive parenting practices at home. Through active parental involvement, there has been a rise in awareness of the importance of character education, effective communication, and empathy. Thus, the parenting program proves to be an effective preventive measure in creating a safe and supportive learning environment for optimal child development.